Advantages of an All-Welded Freight Car Bogie Side Frame - Lobanov, L. M.; Makhnenko, O. V.; Pavlovsky, V. I.; Saprykina, G. Yu.; Pustovoy, A. D. (Science and Transport Progress, 2022)
Purpose. Railway safety during the operation of freight cars largely depends on the reliability, fatigue resistance and durability of the cast bearing elements of the three-element bogie, especially the side frames. Premature failure of cast frames occurs mainly due to undetected latent defects in the foundry. To eliminate these problems, it is advisable to develop an alternative native all-welded side frame for a bogie with an axle load of 23.5 tnf, which can be interchangeable with the cast structure. Methodology. Mathematical modelling approaches were used to determine the stress-strain state of an all-welded structure under the influence of regulated loads and to assess its strength in accordance with current national and modern world standards. Findings. Prototypes of the all-welded side frame structure were subjected to accelerated fatigue tests. The tests have experimentally proved that the cyclic durability of the developed side frame is significantly (2...4 times) higher than the cyclic durability of cast side frames. Originality. A comparative analysis of the permissible stress amplitudes in different zones of the all-welded side frame during long-term operation based on 107 load cycles in accordance with the current standard for the strength of railway cars and modern approaches to determining the fatigue resistance of welded joints showed the insufficient conservatism of the national standard for assessing the fatigue strength of welded joints, which was taken into account when developing a new design of the all-welded side frame. Practical value. In addition to increasing reliability, possible increase in overhaul mileage and warranty period of side frames by ensuring a high level of fatigue resistance and durability, the welded structure can ensure the accuracy of the base frame size, reduce the weight of unsprung masses, which should reduce wheel wear and improve the running characteristics of railway carriage bogies. Reducing the cost of introducing all-welded side frames into mass production compared to the use of foundry technology for the manufacture of these structures and the fact that the cost of manufacturing an all-welded side frame is generally competitive with a cast structure is also one of the important advantages of our developme